Factors affecting generation z’s intention to use virtual banking in Malaysia: a study in the post covid-19 pandemic - Hew, Jun Hung (2022)
Currently, there is still a significant gap in understanding Malaysian Gen Z’s behavioural intention towards virtual banking. However, Gen Z represents a huge customer segment that is targeted by the virtual bank. This study aims to understand the factors that affect Gen Z’s behavioural intention to use virtual banking. Specifically, it examines whether effort expectancy, performance expectancy, social influence, facilitating conditions, hedonic motivation, and trust have positive and significant relationships with behavioural intention, by adapting and extending the Unified Theory of Acceptance and Use of Technology 2. Hypotheses were also formed to examine the relationships. To test the hypotheses, a self-administered questionnaire was prepared and distributed online to the respondents. 483 valid responses were collected and the data was transferred to IBM SPSS Statistics 26 and SmartPLS 3 for analysis. The reliability and validity of the research instruments were tested to ensure the quality of analysis outcomes. Pearson Correlation Coefficient and Multiple Linear Regression were the two analysis methods employed to test the hypotheses. The findings of this research reported that all the factors, except hedonic motivation, play a positive and significant role in determining behavioural intention. Implications from both theoretical and managerial perspectives were discussed. Moreover, the limitations of this research were revealed and recommendations were provided for future research.